Evaluation of the Weightage on Pain Management in Pharmacology Curricula of MBBS Course in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Prioritizing problem-oriented undergraduate medical education is paramount to adequate management of pain in real life scenarios. The present research was conducted with an attempt to explore the important baseline information for pain medicine education and evaluation within pharmacology curricula of MBBS course in Bangladesh.Materials and methods: This descriptive cross-sectional study evaluates the curriculum (Pharmacology of MBBS curriculum, 2012), and written question (SAQ) of MBBS Examination of last ten years extending from January 2010 to November,2019 of all 7 universities offering MBBS degree. The evaluation was conducted through searching certain key phrases.Results: In Pharmacology and Therapeutics portion of the curriculum, only 4 hours and 2 hours are allocated to discuss pain management in lecture and tutorial respectively. In the study period, average marks allocated in pharmacology written question papers was 4.4 (SD ± 2.7) and the difference among studied universities was not significant (p value 0.7).Conclusion: Allocated time in the curricula to teach pain management is very low and weightage received in assessment is also inadequate. Education on pain medication as well as management should receive more emphasis.Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 48-51